A Model for Consumer Acceptance of Insect-Based Dog Foods among Adult UK Dog Owners - Joanne Pinney; Montserrat Costa-Font (Animals, 2024)
The use of alternative proteins is becoming more common in pet feed, and insect-based dog foods (IBDFs) are becoming more widely available. However, little research has been conducted to date in respect of the drivers for consumers’ acceptance of IBDF. This study aimed to investigate the acceptance of IBDF among adult UK dog owners and the factors influencing the decision to try and buy such products. A theoretical model was developed following a review of the existing literature. An online survey of 280 participants was carried out and the results were analysed using structural equation modelling (SEM) to test the theoretical model. The following constructs all had a significant impact on attitudes towards IBDF and/or intentions to try and buy IBDF: food preferences for animal welfare, health and environment; attitudes towards uses of animals; beliefs about insect sentience; disgust; perceptions of benefits and risks; and social norms. Social norms had the strongest influence of any single construct. Consumer acceptance of IBDF is multi-faceted including social, cultural and ethical components, and it is likely that the better availability of information and opportunities for consumers to familiarise themselves with IBDF would help to drive consumer acceptance. In order to allow dog owners to make informed decisions in line with their ethical preferences, further research is needed to establish the overall health and welfare implications of IBDF on the animals involved in production, as well as the companion animals, who are the ultimate consumers.